Art of transition : the field of art in post-Soviet Russia - Herrala, Elise ([Place of publication not identified] : Routledge, 2021)
The dissolution of the Soviet Union brought massive change in every domain of life, particularly in the cultural sector, where artists were suddenly "free" from party-mandated modes of representation, and now could promote and sell their work globally. But in Russia, the encounter with Western art markets was fraught. The Russian field of art still remains on the periphery of the international art world, struggling for legitimacy in the eyes of foreign experts and collectors. This book examines the challenges Russian art world actors faced in building a field of art in a society undergoing rapid and significant economic, political, and social transformation, and traces those challenges into the twenty-first century. Drawing on historical and ethnographic research, Art of Transition traces the ways the field of art has developed, evolved, and been sustained in Russia after socialism. It shows how Russiaś art world has grappled with its Soviet past and negotiated its standing in an unequal, globalized present. By attending to the historical legacy of Russian art throughout the twentieth century, this book constructs a genealogy of the contemporary field of postsocialist art that illuminates how Russians have come to understand themselves and their place in the world.
List of Illustrations Note on TransliterationAcknowledgmentsIntroduction: Toward a Postsocialist Field of Art1. From Last to First: Two Generations of Postsocialist Russian Artists2. Collecting for the Nation3. Building the Field through the Market: The Role of Galleries4. "History is Repeating Itself": Russian Art and the State5. Neither Here nor There: Russia in the Global Art WorldConclusion: The Field of Art in Russia and BeyondIndex
Revision of the author's thesis (doctoral)--2016, University of California, Berkeley, under the title: What's the matter with Moscow? developing a field of art in a postsocialist, global world.
Keywords: ART / Art & Politics; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Sociology / General; Art and society -- Russia (Federation); Post-communism -- Russia (Federation)